Low Caloric Sweeteners for Diabetes and Obesity Care and Their - Mohammad Asif (Research Center for Rational Use of Drugs (RCRUD), 2015)
Diabetes and obesity are two common human disorders that affecting human health and invite various diseases and disorders in normal body functions. These diseases are very common worldwide. Diabetes occurs when high blood sugar levels develop. This happens when body can't make and use all of the insulin it needs to blood sugar normally to keep blood sugar levels as normal as possible to control diabetes. Diabetic patients will need to follow a diet plan, do exercise and possibly take insulin injections. As part of eating plan, health care provider, and dietitian may ask to limit the amount of carbohydrates eat each day. Low-calorie sweeteners are one easy tool to help for follow eating plan. Obesity is more susceptible and often been associated with frequent ingestion of high energy food in high amount and high intake of sugars such as fermentable sugars such as sucrose, fructose, glucose, and maltose. Both diseases are may be genetically or due to hormonal imbalances. High energy sweeteners may causes caries in the teeth particularly susceptible to the children. Increased calorie intake associated with sugars and carbohydrates, especially when associated with physical inactivity, has been implicated in obesity. Fortunately, low calorie artificial and natural alternatives of sugars have been developed as alternatives to fermentable sugars and have shown promise in these health issues. Although there are only few artificial sweeteners (saccharin, aspartame, acesulfam potassium, sucralose, cyclamate) that have been approved as food additives by the Food and Drug Administration and additional other low-caloric sweeteners (sugar alcohols, neotame, stevia, erythritol, xylitol, tagatose) that have FDA-generally recognized as safe. Given the health impact of sugars and other carbohydrates, professionals should be aware of the marketed available low caloric sweeteners and both their benefits and potential risks.